Perceptions diverge on aspects related to substance use disorder: An analysis of individuals in recovery, physicians, nurses, and medical students. Issue 4 (October 2021) - Shreffler, Jacob; Shaw, Isaac; McGee, Suzanne; Bishop, Campbell; Thé, Selena; O'Brien, Daniel; Price, Tim; Huecker, Martin
Background: Interactions with healthcare workers can provide effective entrance into treatment, ensuring retention and lifelong recovery for individuals with Substance Use Disorder (SUD). Healthcare providers approach the challenges of patient management with different skills, comfort levels, and viewpoints. Individuals in recovery also provide crucial perspectives relevant to the complex aspects of the drug epidemic. The purpose of this study was to determine if perceptions of SUD diverge among individuals in recovery, physicians, nurses and medical students. Methods: A survey consisting of 29 Likert statements was deployed to physicians, nurses, medical students, and persons with SUD in recovery. Respondents were asked to rate their level of agreement on statements about SUD such as treatment, stigma, medications for opioid use disorder (MOUD), naloxone kits, safe injection sites, and methamphetamine usage. Separate Welch's analysis of variances (ANOVAs) were conducted to determine differences between the respondent groups and each statement. For any statistically significant findings, Games-Howell post-hoc analyses were employed. Results: A total of 523 individuals provided survey responses: individuals in recovery ( n = 111), physicians ( n = 113), nurses ( n = 206), and medical students ( n = 93). Survey results revealed the majority of items had statistically significant differences in respondent groups. Perceptions diverged on items related to treatment, stigma, MOUD, take-home naloxone kits, safe injection sites, needle exchange programs, and methamphetamine. Conclusion: As healthcare providers and policymakers develop treatment strategies to engage those with SUD in quality treatment, they will benefit from understanding how different viewpoints on SUD affect treatment for these individuals. These attitudes impact stigma, willingness to prescribe new treatments, and development of clinical relationships. The insight from this study allows for important discussions on the substance use health crisis and further inquiry on why these differences exist and how the diverging viewpoints may impact the lives of persons with SUD.